The shape of wine : its packaging evolution - Henry Work (Oxon : Routledge, 2019)
"Grape wine has been produced for at least 4,000 years, having been aged, stored and transported in every conceivable type of vessel. Its seductiveness has been enhanced by this packaging: primarily three strikingly different containers - amphorae, wooden barrels and glass bottles. Henry H. Work brings extensive wine experience as a cooper, working with wine barrels and living in California's Napa Valley to provide a richly detailed and vivid account of wine containers through the ages. This book delves into the history, evolution, and present use of containers, vessels, and stoppers; from animal skin sacks to barrels, from glass bottles to upstart packaging such as wine casks, and even aluminium cans. It considers the advantages and weaknesses of their construction, designs and labels, methods of shipment and storage, as well as their impact on marketing wine to customers. This is an enlightening and innovative read which draws on the most current archaeological research, scientific data and wine business trends. It is richly peppered throughout with the author's own visits to many of the locations explored in the book, bringing history to life. This book will appeal to individuals within the wine industry, undergraduates in the fields of history, archaeology, food and hospitality, as well as all people interested in wine."
Keywords: Amphores; Wine bottles; Wine barrels; TECHNOLOGY & ENGINEERING Food Science